3D-printed bioabsordable polycaprolactone stent: The effect of process parameters on its physical features. (5th January 2018) - Guerra, Antonio J.; Ciurana, Joaquim
Abstract: Biodegradable stents (BRS) offer the potential to improve long-term patency rates by providing support just long enough for the artery to heal. However, manufacture BRS is rather difficult. Nowadays 3D additive manufacturing could be an interesting manufacturing method to produce BRS. In this context, this work presents a novel 3D Additive Manufacturing Machine to be used to manufacture BRSs based on polymers and discusses the effect the process parameters have on the physical features of the BRS. The printing nozzle temperature, flow rate, speed, and trajectories effects on polycaprolactone stents were studied. Printed samples were analysed using Optical Microscopy, Differential Scanning Calorimetry ( DSC ), and the Radial Expansion Test to study the effects printing parameters have on their dimensional precision, material structure distribution, and radial behaviour, respectively. Results showed that the dimensional precision of a BRS is strongly influenced by printing temperature and flow rate, although printing speed did not exert any influence. Printing parameters did not significantly influence the structure of the materials. Furthermore, the samples, with an average expansion ratio of 320% and around 22% of recoil ratio, showed good radial behaviour. Graphical abstract: Highlights: A novel 3D Additive Manufacturing Machine to bioabsordable polymeric stents is presented. The 3D-printing process has leave strong effects over the dimensional precision. The 3D-printing process has leave lesser effects over the material structure. 3D-printed stents have shown good radial behaviour (320% of expansion and a 22.78% of recoil).